Penanganan Kemacetan Lalu Lintas Yang Ditimbulkan Akibat Pergerakan Putar Balik (U-Turn) Pada Jalan Perkotaan - Wadu, Amy; Dumin, Ludofikus; Nahak, Priska Gardeni (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
The massive increase in the number of vehicles has placed a huge burden on urban transport infrastructure. This has created an urgent need for effective strategies to address traffic congestion. In Kupang City, U-turn facilities in the median of major roads such as Piet A. Tallo Street, have become a cause of congestion due to the delays that occur when vehicles make a U-turn. Approaching vehicles are often forced to slow down to allow the U-turning vehicles to merge. In an effort to respond to the growing demands of traffic flow, this study aims to investigate the impact of U-turn facilities on road medians and provide recommendations that can improve the efficiency and smoothness of traffic on urban roads. Using VISSIM software, the simulation of the planned improvement scenario of closing U1, U2 and U3 and diverting them to U4 and improving the geometry of U4 with outer widening was carried out. The results showed that the delay only reached 15.46 seconds/vehicle with level of service C from the previous existing conditions which reached 65.15 seconds/vehicle with level of service F